The relationship between a primary maxillary incisor with a talon cusp and the permanent successor: a study of 57 cases - CHUN-KEI LEE, NIGEL MARTYN KING, EDWARD CHIN-MAN LO, & SHIU-YIN CHO (IAPD and Blackwell, 2007)
Most reported cases of talon cusps in the primary dentition have been on the maxillary central incisors and the permanent successors have remained unaffected. Four of the five reported cases on a maxillary lateral incisor, however, have been associated with a supernumerary permanent successor.